The discourse of financial and international cooperation organizations on the compulsory nature of lower secondary education, 1960-2015. A perspective from discursive institutionalism and critical discourse analysis - Rosalina Romero Gonzaga (Arizona State University, 2019)
The article examines the proposals and recommendations formulated by three international financial and cooperation organizations (OFyCIs) for lower secondary education (ESB), an emerging educational level in educational research. It is assumed that the lower secondary school is promoted by the OFyCI as a functional subsidiary to upper secondary education (high secondary education), reoriented and aligned toward the capitalist economy, but forgoing a critical and comprehensive development of adolescents. The discourse of the OFyCI on the compulsory nature of secondary education constitutes frames of reference that serve to reproduce their economic, political and social interests, within a context marked by educational segmentation and lack of definition of educational levels.